Ergonomics and Physiological Impacts on Running Athletes: A Systematic Review - Putri, Catherine Dwi Augusthi; Arwan Bin Laeto; Nuha Mardhiyah Salsabilah; Nadira Alifa, Nadira Alifa; Muhammad Abdurrahman Ahnaf (Universitas Pekalongan, 2025)
Running is a sport that is often chosen by many people when they want to exercise. Both professional and amateur runners often experience musculoskeletal disorders such as knee, ankle, and hip pain due to repetitive mechanical stress, improper running technique, and the use of non-ergonomic footwear. In running, ergonomic interventions—including modifications to running posture, shoe selection, and corrective exercise programs — are considered important for injury prevention and performance enhancement, but their effectiveness varies across studies. This research aims to evaluate the effectiveness of ergonomic interventions on musculoskeletal health and performance in runners. The Research methode with literature search was conducted through PubMed, Scopus, and Science Direct databases (2020–2025) and yielded 37 articles. Of the screened articles, three studies met the inclusion criteria. Data were analyzed narratively, with risk of bias assessment performed using RoB 2 and ROBINS-I tools. The Result :. Interventions such as running style analysis, dynamic posture training, and the use of ergonomic shoes have been shown to reduce the prevalence of overuse injuries such as iliotibial band syndrome and plantar fasciitis. Several studies have also reported improvements in running efficiency, VO₂ max, and travel time. Runners who take an individualized ergonomic approach show faster injury recovery and higher performance consistency. Ergonomic interventions have been proven effective in reducing the risk of musculoskeletal injuries and improving runners' performance. The recommendations that the author proposes for training management and athlete health are as follows: integrating neuromuscular strengthening exercises into running programs; optimizing training load regulation and recovery to prevent overtraining; utilizing technology-based psychological interventions to maintain motivation and training adherence; employing hypoxic training conditions or environmental simulations as physiological interventions; using wearable devices for real-time monitoring; and conducting regular physiological screenings as strategies for injury prevention and performance enhancement